2013
DOI: 10.1002/chem.201203998
|View full text |Cite
|
Sign up to set email alerts
|

Polymer‐Templated Perylene‐Probe Noncovalent Self‐Assembly: A New Strategy for Label‐Free Ultrasensitive Fluorescence Turn‐On Biosensing

Abstract: A new label-free fluorescence turn-on strategy for highly sensitive biosensing has been developed. A negatively charged perylene probe was synthesized. Polycations could induce aggregation of the perylene probe through noncovalent interactions and the fluorescence of the probe's monomer was efficiently quenched. Upon addition of a single-stranded nucleic acid, competitive binding of the negatively charged nucleic acid (a polyanion) to the cationic polymer resulted in the release of a monomer and thus a turn-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…40 In the buffer solution, PDI-DHA displays unique monomer emission with peaks at 548 and 587 nm. The amphiphilic compound lauroylcholine was employed to be a good substrate for AChE and introduce the PDI-DHA aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In the buffer solution, PDI-DHA displays unique monomer emission with peaks at 548 and 587 nm. The amphiphilic compound lauroylcholine was employed to be a good substrate for AChE and introduce the PDI-DHA aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…40 Lauroylcholine was bought from Aladdin (Shanghai, China). Lauric acid was purchased from Dayang Chemicals Co., Ltd. Trypsin and acetylcholinesterase was ordered from Sigma.…”
Section: Materials and Measurementsmentioning
confidence: 99%
“…The 1 H NMR results were compared with the literature data, thereby it further confirmed the correct structure. 23,34 The characterization data of PBI were as follows: 1 Fig.2(b), shows that the proton resonances belonging to -OH of the PBI-HPG could be found at 2.09 ppm and the proton resonances of -CH 2 -and -CH-of hyperbranched polyglycidyl were observed at 3.49-4.23 ppm. 24 Fig.3(a) shows the zeta potential of the PBI-HPG/RGO measured at different pH in distilled water.…”
Section: Characterization Of Pbi-hpg/rgomentioning
confidence: 97%
“…Then the dark-red precipitate was washed with deionized water until the filtrate was at a nearly neutral pH value. 23 The product was dried at 60 o C in a vacuum drying oven to gain a red brown powder.…”
Section: Synthesis Of the Perylene Bisimide Derivatives (Pbi)mentioning
confidence: 99%
“…Poly(diallyldimethylammonium chloride) (PDADMAC) is a water‐soluble cationic polyelectrolyte with quaternary ammonium groups . Anionic dyes can interact with PDADMAC by electrostatic interactions to have the potential to form their self‐aggregate and show distinct spectroscopic and sensing properties from those of monomeric dyes . Our previous study reported that a chemosensor through the electrostatic combination of an anionic organic dye, pyrogallol red (PR), and PDADMAC exhibited a colorimetric selective detection for Zn 2+ distinct from PR .…”
Section: Introductionmentioning
confidence: 99%